Assessing live microbial therapeutic transmission - Jeremiah J. Faith (Gut Microbes)
The development of fecal microbiota transplantation and defined live biotherapeutic products for the treatment of human disease has been an empirically driven process yielding a notable success of approved drugs for the treatment of recurrent Clostridioides difficile infection. Assessing the potential of this therapeutic modality in other indications with mixed clinical results would benefit from consistent quantitative frameworks to characterize drug potency and composition and to assess the impact of dose and composition on the frequency and duration of strain engraftment. Monitoring these drug properties and engraftment outcomes would help identify minimally sufficient sets of microbial strains to treat disease and provide insights into the intersection between microbial function and host physiology. Broad and correct usage of strain detection methods is essential to this advancement. This article describes strain detection approaches, where they are best applied, what data they require, and clinical trial designs that are best suited to their application.